Sustainable food science a comprehensive approach - Ferranti, Pasquale (Elsevier, 2023)
Sustainable Food Science: A Comprehensive Approach provides a timely resource on new materials and ingredients currently available in the food industry, along with cutting-edge research on how to develop and secure sustainable food for a growing world population. With contributions from international experts and an outstanding editing team, the book covers sustainable sources of ingredients for the food industry, i.e., pulses, soybeans, peanuts, along with prospective and emerging sources such as industrial hemp, insects, algae, etc. In addition, other sections cover sustainable processes for new food sources and new food design, such as microbiological and biotechnological processes and dairy and meat substitutes. Users will value the clear-cut, in-depth and expert assessment of each topic and appreciate its sensible and logical hierarchical structure. This reference work will provide expert guidance for food scientists of all levels - both in academia or industry.